Anotated Checklist of Chinese Ensifera: The Gryllacrididae - Bian, Xun; Liu, Jing; Yang, Zizhong (Zootaxa, 2021)
This paper lists all known Chinese Raspy Crickets (Gryllacrididae) following the scheme proposed by Cadena-Castañeda. A total of 23 genera, 104 species, 3 new combinations, 4 new synonyms, and 1 new replacement name are recorded. Based on these known species, keys to genera (or subgenera) and species with the diagnosis of each genus are also given. Also we provide the Chinese name of all categories.